Nutrition and Mental Health Empowerment Project for Counseling Teachers and Students of Senior High Schools in Yogyakarta - Risky Oktriani; Dianandha Septiana Rubi; Yogik Onky Silvana Wijaya; Bira Arumndari Nurrahma; Mohamad Fay Faizal; Sarair Maulidya; Brilliant Alendra Adianfra; Irwan Supriyanto; Edilburga Wulan Saptandari; Arta Farmawati; Sunarti Sunarti (Journal of Community Empowerment for Health, 2023)
Background: Mental disorders can affect people of any age, including teenagers of school age, which can disrupt their productivity and quality of life if not managed properly. There is growing evidence that nutrition is vital in mental health, which helps manage mental disorders. Simple interventions for mental disorders among teenagers through health promotion, education, and nutritional interventions are needed to prevent mental disorders or provide early treatment for those in need.Objective: Our project aimed to train counseling teachers and students of senior high schools in Yogyakarta to have the capability of performing simple management of mental disorders and promoting a healthy nutritional status.Methods: Our project consisted of three phases; phase I (webinar and workshop), phase II (practice and implementation at schools), and phase III (monitoring and evaluation). We used pre- and post-tests to assess respondents’ knowledge and questionnaires to assess their perceptions of the project.Results: Twenty counseling teachers and forty students from 20 senior high schools in Yogyakarta participated in this project. Our project slightly improved students' knowledge of the importance of nutrition and mental health but not the teachers’ knowledge. All participants welcomed our project positively. Most participants agreed they learned new and important information and stated that the project helped combat nutritional problems and mental disorders.Conclusion: Our project was perceived positively and improved participants’ skills and knowledge of nutrition and mental health issues. This suggests that the project has empowered them to perform basic management of nutritional problems and mental disorders among teenagers at their schools. Additionally, more projects are still needed to widen and maximize the coverage of these important topics.